Efficacy of Creamatocrit Technique in Evaluation of Premature Infants Fed With Breast Milk - Hsiang-Yu Lin; Hsin-Yang Hsieh; Hung-Hsin Chen; Hsiao-Yu Chiu; Hung-Chih Lin; Bai-Horng Su (Elsevier, 2011)
Most premature babies are discharged with low body weight. Creamatocrit represents the lipid concentration of breast milk. We expected the creamatocrit technique could be applied in the nutrition plan for premature infants who were exclusively fed by human milk. Methods: Breast milk samples were obtained from the mothers whose babies were admitted to the neonatal intensive care unit or sick baby room. The breast milk provider was enrolled under the criteria of stable breast milk expression 2 weeks after having given birth. Breast milk was collected for 7 consequent days. Creamatocrit technique and calorie analysis were performed on the processed breast milk samples. Results: Fourteen pairs of mothers and infants were enrolled in our study. The median gestational age and birth weight were 29 weeks (27-36 weeks) and 1393 g (680-3050 g), respectively. The mean calorie and creamatocrit values for all the 98 breast milk samples were 0.67 kcal/mL and 5.98%, respectively. The linear correlation between creamatocrit value and laboratory-measured calories was found to be calories (kcal/mL)=0.39+0.048×creamatocrit (%) (p<0.05). Conclusion: We established the relation equation of creamatocrit and calories for the first time in Chinese population, which is convenient and accurate for evaluating calories provided for premature infants fed with breast milk.